2011
DOI: 10.1051/epjap/2011110082
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier formation at the Au to rare earth doped GaN thin film interface

Abstract: Abstract. The Schottky barriers formed at the interface between gold and various rare earth doped GaN thin films (RE = Yb, Er, Gd) were investigated in situ using synchrotron photoemission spectroscopy. The resultant Schottky barrier heights were measured as 1.68 ± 0.1 eV (Yb:GaN), 1.64 ± 0.1 eV (Er:GaN), and 1.33 ± 0.1 eV (Gd:GaN). We find compelling evidence that thin layers of gold do not wet and uniformly cover the GaN surface, even with rare earth doping of the GaN. Furthermore, the trend of the Schottky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…The X-ray diffraction (XRD) patterns of Gd, Er, and Yb doped GaN films show c-axis orientation and a high degree of crystallinity. The presence of any secondary phases or spurious peaks has not been observed, as described elsewhere [18]. Slight shifts in diffraction peak positions toward lower Bragg angles have been observed with Er doped GaN grown on Al 2 O 3 (0 0 0 1) substrates and RE x Ga 1−x N thin films (50-300 nm) fabricated on Si(1 1 1) (RE = Gd, Yb), which is indicative of some lattice expansion, as is expected [26].…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The X-ray diffraction (XRD) patterns of Gd, Er, and Yb doped GaN films show c-axis orientation and a high degree of crystallinity. The presence of any secondary phases or spurious peaks has not been observed, as described elsewhere [18]. Slight shifts in diffraction peak positions toward lower Bragg angles have been observed with Er doped GaN grown on Al 2 O 3 (0 0 0 1) substrates and RE x Ga 1−x N thin films (50-300 nm) fabricated on Si(1 1 1) (RE = Gd, Yb), which is indicative of some lattice expansion, as is expected [26].…”
Section: Methodsmentioning
confidence: 90%
“…Due to their highly localized 4f electrons [16,17], the direct f -f interactions between the neighboring rare earth atoms are very weak and nonexistent in a weakly doped semiconductor host. In addition, rare earth doping is seen to increase the gold electrode Schottky barrier heights significantly [18] thereby decreasing leakage currents in particle type detector devices.…”
Section: Introductionmentioning
confidence: 99%
“…98,99 A rare-earth-doped GaN thin film might lead to significant improvements in device performance in sensor applications; GaN is potentially neutron sensitive when doped with Gd. 100,101 Melton et al 102 found that the carrier concentration in Gd-doped GaN increases as a result of the Gd doping. Cao and Myers employed a 500-nm superlattice doping structure grown by MBE to maintain the quality of the material.…”
Section: Neutron Detectionmentioning
confidence: 99%
“…A detailed description of the MBE with ultra-high vacuum (UHV) system, K cells, a quartz crystal thickness monitor, low energy electron diffraction (LEED) camera, heater can be found in many articles. [11][12][13][14]30,31 Briefly, the deposition UHV chamber was first pumped down to base pressure of 10 −10 torr, while substrate was annealed at 900 • C for 30-60 minutes in order to remove most impurity or residue gas. Before Si substrates were placed into the chamber, they were ultrasonically washed in the methanol solution followed by standard cleaning.…”
Section: Synthesis and Basic Characterization Of Gan Thin Filmsmentioning
confidence: 99%
“…Higher electron mobility and electron saturation velocity allow for higher frequency of operation, and fast responsivity. 3,4 To date, the synthesis of different types of GaN materials have been performed by using various technical routes, including pulsed laser deposition techniques, 5 electrochemical techniques, 6 hot filament chemical vapor deposition (HFCVD), 7 plasma enhanced CVD, 8 sputtering method, 9 spin coating method, 10 and molecular beam epitaxy (MBE), [11][12][13][14] among others.…”
Section: Introductionmentioning
confidence: 99%